2019
DOI: 10.1021/acssuschemeng.9b05231
|View full text |Cite
|
Sign up to set email alerts
|

Direct Surface Functionalization of Cellulose Nanocrystals with Hyperbranched Polymers through the Anionic Polymerization for pH-Responsive Intracellular Drug Delivery

Abstract: Cellulose nanocrystals (CNCs) are one of the most promising natural derived nanomaterials that possess a number of advantages such as nanoscale size, rich of surface functional groups, biodegradability, low cost, and desirable biocompatibility. Considering the above characteristics, CNCs and their composites have raised considerable research attention for various applications. On the other hand, the surface modification of nanomaterials plays a crucial role in adjusting their surface properties and endow novel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(18 citation statements)
references
References 53 publications
0
17
0
Order By: Relevance
“…For instance, Wan et al developed a new approach to prepare hyperbranched polymers-functionalized CNCs through direct anionic polymerization utilizing glycidol as the monomer and surface hydroxyl groups of CNCs as initiator. The peripheral end functional groups of the modified CNCs were then converted to hydrazide groups, which could be used for loading anticancer drugs, such as epirubicin, through the formation of hydrazone bonds with pH-responsiveness (Wan et al, 2019). The authors suggested that epirubicin could be released from CNCs-based carriers with pH-responsive behavior and that the obtained drug-containing complexes could preserve their anticancer capability.…”
Section: Nanocellulose For Biomedical Applicationsmentioning
confidence: 99%
“…For instance, Wan et al developed a new approach to prepare hyperbranched polymers-functionalized CNCs through direct anionic polymerization utilizing glycidol as the monomer and surface hydroxyl groups of CNCs as initiator. The peripheral end functional groups of the modified CNCs were then converted to hydrazide groups, which could be used for loading anticancer drugs, such as epirubicin, through the formation of hydrazone bonds with pH-responsiveness (Wan et al, 2019). The authors suggested that epirubicin could be released from CNCs-based carriers with pH-responsive behavior and that the obtained drug-containing complexes could preserve their anticancer capability.…”
Section: Nanocellulose For Biomedical Applicationsmentioning
confidence: 99%
“…Among them, nanocellulose is a renewable, biodegradable, and natural biopolymer that has considerable application prospects in drug delivery systems. For instance, Wan et al [333] designed an effective method for designing hyperbranched polymerfunctionalized CNCs without direct anionic polymerization (Figure 22a). The end groups of the resulting functionalized CNC surface are further converted to acylhydrazide groups, which can be applied to load anticancer drugs, such as epirubicin (EPI), by forming pH-responsive hydrazone bonds.…”
Section: Nanocellulose-based Drug Deliverymentioning
confidence: 99%
“…1 Nanocellulose as multifunctional delivery vehicle. Nanocellulose could be utilized for sustained delivery of therapeutic molecules, such as anti-microbial drugs [ 40 ], as a wound healing agents [ 41 ], anti-cancer drugs [ 42 ], and various hemostatic agents [ 43 ]. Nanocellulose has also been shown to deliver nucleic acids [ 44 , 45 ], proteins [ 46 ], and certain growth promoting factors for tissue engineering [ 47 ].…”
Section: Introductionmentioning
confidence: 99%